Evaluasi Jaringan Drainase Menggunakan Software EPA SWMM pada Perumahan Singgalang Green Residence Kota Pekanbaru - Bayu Bastanta Tarigan; Virgo Trisep Haris; Lusi Dwi Putri (Jurnal Teknik Sipil Unaya, 2023)
This research was conducted to determine the drainage capacity of the Pekanbaru City Singgalang Green Residence Housing so that it can function optimally. The research location is at the Singgalang Green Residence Housing Pekanbaru City has a channel with a square shape and 9 different dimensions. In this study, the EPA SWMM 5.1 program was used to simulate channel conditions when rain occurs. The data needed in this study are data on rainfall that occurred for ten years and the results of surveys in the field. After obtaining all the data needed, the next step is to process the data with the right theory to get the result data which will then be inputted into the EPA SWMM 5.1 application. From the simulation results, a peak discharge runoff of 0,01 – 0,09 m3/s was obtained. The results of the study showed that of the 9 channels contained in the Singgalang Green Residence Housing in Pekanbaru City, there were 6 channels that were flooded during the rain so that they could not drain water optimally. Based on the results of the study, it can be concluded that the dimensions of the drainage channel at the Singgalang Green Residence Housing in Pekanbaru City are not able to drain water discharge.